The rapid rise in domestic value chains of nutrient-dense foods (fruits, vegetables, and animal products) in Sub-Saharan Africa: Policy implications - Reardon, Thomas; Liverpool-Tasie, Lenis Saweda; Belton, Ben; Dolislager, Michael; Minten, Bart; Popkin, Barry M.; Vos, Rob (International Food Policy Research Institute, 2023)
Despite African consumers under-consuming nutrient dense fruits and vegetables (FV) and animal products (AP), and the farm production and supply chains of these products are fraught with constraints that keep them from operating optimally, we find abundant recent evidence of dynamism in these sectors. To wit: (1) consumption of these products in levels and shares is already substantial and growing rapidly; (2) supply of these products is growing rapidly, just not yet much faster than population growth; (3) supply growth is manifested in a number of countries by dynamic “meso booms” with diffusion of farming and growth in midstream ("Hidden Middle") value chain segments; these booms are “grassroots” driven, without subsidy or management by government or NGOs or large companies. We reviewed recent survey-based evidence of these booms and discussed the drivers. The policy implications are the need for governments to invest in the conditions we found to be enabling these booms, that is, roads and wholesale markets and electrification and other infrastructure hard and soft.